2023
DOI: 10.1021/jacs.2c11643
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Coordinated Inner-Sphere CO2 Electroreduction at Au–Water Interfaces

Abstract: Electrochemical CO2 reduction reaction (CO2RR) is a promising technology for the clean energy economy. Numerous efforts have been devoted to enhancing the mechanistic understanding of CO2RR from both experimental and theoretical studies. Electrolyte ions are critical for the CO2RR; however, the role of alkali metal cations is highly controversial, and a complete free energy diagram of CO2RR at Au–water interfaces is still missing. Here, we provide a systematic mechanism study toward CO2RR via ab initio molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 70 publications
3
55
0
Order By: Relevance
“…For simplicity, we assumed that these conclusions hold also for all other considered metal surfaces, an approximation that has to be verified by future simulations. In line with our settings, a recent work has suggested that the transition state of the *CO 2 to *COOH step lies close to *COOH with no additional kinetic barrier, but proposed an additional barrier for CO 2 adsorption which we did not consider here 130 .…”
Section: Methodssupporting
confidence: 88%
“…For simplicity, we assumed that these conclusions hold also for all other considered metal surfaces, an approximation that has to be verified by future simulations. In line with our settings, a recent work has suggested that the transition state of the *CO 2 to *COOH step lies close to *COOH with no additional kinetic barrier, but proposed an additional barrier for CO 2 adsorption which we did not consider here 130 .…”
Section: Methodssupporting
confidence: 88%
“…Ab initio molecular dynamics (AIMD) provides direct atomistic level insights on adsorption phenomena and catalysis at metal|water interfaces [31][32][33][34][35][36][37] . For instance, Heenen et al studied the adsorption of several common adsorbates (CO*, CHO*, COH*, OCCHO*, OH* and OOH*) on Cu, Au and Pt metal|water interfaces, and found the solvation energies to be dependent on both the identity of the adsorbate and the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Despite the widespread observation of cation effects on the CO2RR, the mechanistic basis for these trends remains the subject of intense debate. [8][9][10][11][12][13][14][15][16][17][18][19][20] Leading explanations put forward bifurcate into two broad categories: (a) cations induce changes to the mean-field electrostatic potential profile at the interface; [15][16][17][18] and (b) cations are involved in coordinative chemical interactions with adsorbed reaction intermediates. 11,12,19,21 The former electrostatic model postulates a sharper electrostatic potential drop in the presence of weakly hydrated cations such as Cs + relative to strongly hydrated ions such as Li + .…”
Section: Introductionmentioning
confidence: 99%